Kesenian Tradisional Masukkiri Masyarakat Bugis Pagatan Kecamatan Kusan Hilir Kabupaten Tanah Bumbu - Jannah, Miftahul; Effendi, Rusdi; Susanto, Heri (Prabayaksa: Journal of History Education, 2021)
Kusan Hilir, Tanah Bumbu Regency, has music that is produced from the social order of the Bugis Pagatan. The existence of Islamic values and sticking to customs and culture in the community, then created Islamic nuanced music called Masukkiri. This study aims to find out how the Masukkiri art was born, when the art performance was held, and what values are contained in the traditional art of Masukkiri, the Bugis Pagatan community, Kusan Hilir District, Tanah Bumbu Regency. This study uses historical research methods which are divided into four stages, namely heuristics or collection of sources, criticism or determination of the authenticity of sources, interpretation or interpretation, and historiography as the final stage of writing. The collection of oral sources from the perpetrators and informants was carried out by the interview method, while the collection of written sources used the library method, in the form of books, articles, and journals that were relevant to the object under study. The results of this study, it is known that the emergence of the traditional art of Masukkiri was motivated by the celebration of the Birthday of the Prophet Muhammad SAW, which was packaged with Bugis rhythms and is estimated to have developed since the 20th century along with the Pagatan Kingdom. The traditional art of Masukkiri is held to accompany important events by the Bugis Pagatan community. However, in its development, Masukkiri underwent several changes that were influenced by the times and social conditions in the Bugis Pagatan community itself.